Development of Information System Classification of Community Complaints Based on Keyword Case Study: District Pangandaran - Ramdani, Cecep Muhamad Sidik; Rachman, Andi Nur (Journal of Applied Information System and Informatic (JAISI), 2024)
The growing technology of the public complaint system requires the development to solve the problems that exist in Pangandaran Regency. One of the problems is not applying the classification of complaints based on keywords. So that people still have difficulty understanding the functions of government agencies correctly because there are several government agencies that have similar functions. The development of the complaints system can minimize these errors. System development used is the Extremme Programming method which has four frameworks including planning, design, coding and testing, using UML modeling (Unified Modeling Language). Extreme Programming is the development of the previous method, the Agile method. For testing applications using Black Box Testing is done only to observe the results of execution through test data and check the functional of the software. So that the results obtained are classifiers of public complaints that are directly conveyed to the relevant agencies running well.